Electrospinning fabrication and luminescence properties of Lu2O2S:Eu3+ fibers. Issue 4 (10th January 2017) - Zhang, Bowen; Zou, Haifeng; Song, Yanhua; Guan, Hongxia; Zhou, Xiuqing; Shi, Zhan; Sheng, Ye
Abstract : Lu2 O2 S:Eu 3+ fibers were successfully prepared via an electrospinning method followed by a subsequent two-step calcination process. Abstract : Luminescent one-dimensional Lu2 O2 S:Eu 3+ fibers were successfully prepared via an electrospinning method followed by a subsequent two-step calcination process for the first time. Scanning electron microscopy (SEM) showed that the as-obtained samples present a fiber-like morphology with uniform size and the diameters of the fibers changed from microscale to nanoscale with the increase of Eu 3+ concentration. The emission spectra indicated that the obtained Lu2 O2 S:Eu 3+ fibers exhibited typical Eu 3+ ( 5 D0 – 7 F J ) red emission under ultraviolet excitation and the concentration quenching effects occurred in the fibers composed of 3 mol% Eu 3+ . The decay kinetics behaviors of the Lu2 O2 S:Eu 3+ fibers were investigated, which showed that the fibers composed of 3 mol% Eu 3+ also had the longest lifetime. The spectral characteristics and Eu–O ligand behavior were discussed through Judd–Ofelt parameters such as intensity parameters ( Ω 2, Ω 4 ), radiative transition probability ( A RAD ), radiative lifetime ( τ rad ), and branching ratio ( β 0 J ). In addition, the energy-dispersive X-ray spectra (EDS), thermogravimetry-differential thermal analysis (TG-DTA) and the formation mechanism were also displayed in order to better understand the work.